Effect of plant growth regulators and thiourea on growth, yield and quality of bottle gourd cv. Pusa summer prolific long (Indian Journal of Arid Horticulture, 2025)
The present experiment was carried out on Bottle gourd cv. Pusa summer prolific long during kharif season 2012 with objective to know the effect of plant growth regulators and thiourea on growth, yield and quality of bottle gourd. The treatment comprised of plant growth regulators and thiourea, viz. T, (control), T, (100 ppm NAA), T, (200 ppm NAA), T, (300 ppm NAA), T.(150 ppm Ethrel), T, (300 ppm ethrel), T, (450 ppm ethrel), T, (100 ppm CCC), T, (200 ppm CCC), T, (300 ppm CCC), To (250 ppm thiourea), T,, (500 ppm thiourea), T,, (750 ppm thiourea) were replicated three times in a randomized block design keeping plot size of 6 m x 3 m. Regarding growth parameter. The exogenous application of NAA 300 ppm (T,) recorded maximum vine length (6.80 m), nodes per vine (22.01) and leaf area (274.00 cm). The CCC 300 ppm (T,) treatment produced maximum primary branches (22.97) and secondary branches (9.30) per vine but minimum vine length (4.36 m), nodes per vine (18.05) and leaf area (203.26 m3) were observed in this treatment. The results showed that ethrel 450 ppm significantly increased female flower (22.65), fruit length (61.50 cm), fruit set (67.11%), fruit retention (50.20%), fruit weight (1.311 kg) fruit yield per vine (7.55 kg) and per hectare (549.84 g), net return (212120 per hectare) and B:C ratio (3.38). All over the results showed that most effective treatment for increasing the fruit growth and yield of bottle gourd was ethrel 450 ppm with cost benefit ratio (3.38).
Keywords: Thiourea; Etherel; NAA